From Social Innovation toward the Paradigm of New Public Governance - Čančarević, Danka (Political Life, 2025)
The paper explores the relationship between social innovation and the concept of New Public Governance (NPG) as the dominant paradigmatic framework of contemporary public administration. In the context of globalization, social crises, and increasing societal risks, public policies are increasingly relying on networks, partnerships, and multi-actor collaboration. Social innovations, emerging from community initiatives or through cooperation between public, private, and civil sectors, represent a potential for transforming traditional modes of governance. Based on the assumption that social innovations are not a governance model per se but become part of it through institutionalization and integration into public policies, the paper aims to highlight their role in shaping New Public Governance and improving the effectiveness of public service delivery.